Birefringent effects in plastic optics - Adhikari, Achyut (2017)
Plastic optics are seeing increased usage in various imaging and non-imaging applications due to its low cost, ease of manufacturing and complex parts assembly. Non-imaging applications were the initial foray for plastic optics as the aberration and thermal effects were not important. However, recently there is an increased usage in imaging applications of plastic optics due to ease of manufacturing especially in aspheric profiles. This has brought aberrations to the forefront and more importantly birefringence effects have become critical as well. In this thesis, the birefringent effects in plastic optics are explored with a measurement purpose and its effects on imaging. This study has three main aspects. Firstly, there is a need to incorporate birefringent effects in optical design such that its effects could be modelled and simulated. This is accomplished by optical modelling software ZEMAX and simulated with finite element modelling tool ABAQUS to obtain birefringence in the optical element. The low birefringence polarimeter is designed and developed at COLE (Centre for optical and laser engineering) to measure birefringence. Enhancement of system and the calibration procedure of sample materials is discussed and analysed in detail. Theoretical, experimental and simulation of birefringence in plastic optics is carried out and their results are in good agreement. In the second phase, the cause and measurement of birefringence are rigorously investigated. Birefringence measurement of different injection moulded optical materials like microwell plate, microfluidic channels, optical windows, etc. were carried out. The standard calibration procedure for microfluidic channels and optical elements is performed for qualitative and quantitative analysis. In the third phase, the system is rigorously investigated and aimed for further improvements. Improved methodologies for automated data gathering and processing are proposed and implemented. Further, mathematical relationship and algorithm are optimised for rapid data acquisition and computation. The designed system is cheap, automatic and convenient for the prospective researchers in rapid quality testing labs. While birefringent effects in plastic optics are thoroughly investigated, other applications which involve plastics will benefit from this study. Birefringence primarily occurs due to residual stress induced during the manufacturing processes especially in injection moulding and 3D printing method. Microfluidics and the disposable medical device is hugely affected by residual stress. Effects and techniques to reduce induced birefringence is quantitatively assessed by exploiting the polarimetric methods explained herein.